Does transparency reduce favoritism and corruption? Evidence from the reform of figure skating judging - Zitzewitz, E. (Journal of Sports Economics, 2014)
Transparency is usually thought to reduce favoritism and corruption by facilitating monitoring by outsiders, but there is concern it can have the perverse effect of facilitating collusion by insiders. In response to vote trading scandals in the 1998 and 2002 Olympics, the International Skating Union (ISU) introduced a number of changes to its judging system, including obscuring which judge issued which mark. The stated intent was to disrupt collusion by groups of judges, but this change also frustrates most attempts by outsiders to monitor judge behavior. The author finds that the "compatriot-judge effect," which aggregates favoritism (nationalistic bias from own-country judges) and corruption (vote trading), actually increased slightly after the reforms.